Math Problems

MathematicsPrecalculusQuadratic Equations → Factor Quadratic Equations

Factor each quadratic equation

## Questions

 $$y = x^2 + 11 x + 30$$ $$y = x^2 + 4 x -5$$ $$y = x^2 -x$$ $$y = 3 x^2$$ $$y = x^2 + 2 x -8$$ $$y = x^2 + 2 x -15$$ $$y = 2 x^2 -2$$ $$y = x^2 -16$$ $$y = x^2 -x -30$$ $$y = x^2 -12 x + 36$$ $$y = x^2 + 7 x + 6$$ $$y = x^2 + 9 x + 18$$ $$y = x^2 -3 x$$ $$y = 2 x^2 -5 x + 3$$ $$y = x^2 -25$$ $$y = 4 x^2 -5 x -6$$ $$y = 4 x^2 + 15 x + 9$$ $$y = 3 x^2 -5 x -2$$ $$y = 2 x^2$$ $$y = x^2 + x -6$$ $$y = x^2 + x -20$$ $$y = x^2 + 8 x + 16$$ $$y = x^2 + 9 x + 18$$ $$y = 4 x^2 -13 x + 3$$ $$y = 4 x^2 -8 x$$ $$y = 2 x^2 -4 x$$ $$y = x^2 + x$$ $$y = x^2 -6 x + 9$$

## Answers

 $$y = x^2 + 11 x + 30$$ ⇒ $$(x + 6)(x + 5)$$ $$y = x^2 + 4 x -5$$ ⇒ $$(x + 5)(x -1)$$ $$y = x^2 -x$$ ⇒ $$(x -1)(x)$$ $$y = 3 x^2$$ ⇒ $$3(x)(x)$$ $$y = x^2 + 2 x -8$$ ⇒ $$(x -2)(x + 4)$$ $$y = x^2 + 2 x -15$$ ⇒ $$(x + 5)(x -3)$$ $$y = 2 x^2 -2$$ ⇒ $$2(x -1)(x + 1)$$ $$y = x^2 -16$$ ⇒ $$(x -4)(x + 4)$$ $$y = x^2 -x -30$$ ⇒ $$(x -6)(x + 5)$$ $$y = x^2 -12 x + 36$$ ⇒ $$(x -6)(x -6)$$ $$y = x^2 + 7 x + 6$$ ⇒ $$(x + 6)(x + 1)$$ $$y = x^2 + 9 x + 18$$ ⇒ $$(x + 6)(x + 3)$$ $$y = x^2 -3 x$$ ⇒ $$(x -3)(x)$$ $$y = 2 x^2 -5 x + 3$$ ⇒ $$(2 x -3)(x -1)$$ $$y = x^2 -25$$ ⇒ $$(x -5)(x + 5)$$ $$y = 4 x^2 -5 x -6$$ ⇒ $$(4 x + 3)(x -2)$$ $$y = 4 x^2 + 15 x + 9$$ ⇒ $$(4 x + 3)(x + 3)$$ $$y = 3 x^2 -5 x -2$$ ⇒ $$(3 x + 1)(x -2)$$ $$y = 2 x^2$$ ⇒ $$2(x)(x)$$ $$y = x^2 + x -6$$ ⇒ $$(x + 3)(x -2)$$ $$y = x^2 + x -20$$ ⇒ $$(x + 5)(x -4)$$ $$y = x^2 + 8 x + 16$$ ⇒ $$(x + 4)(x + 4)$$ $$y = x^2 + 9 x + 18$$ ⇒ $$(x + 3)(x + 6)$$ $$y = 4 x^2 -13 x + 3$$ ⇒ $$(4 x -1)(x -3)$$ $$y = 4 x^2 -8 x$$ ⇒ $$4(x)(x -2)$$ $$y = 2 x^2 -4 x$$ ⇒ $$2(x)(x -2)$$ $$y = x^2 + x$$ ⇒ $$(x + 1)(x)$$ $$y = x^2 -6 x + 9$$ ⇒ $$(x -3)(x -3)$$
Problem Set Filters:

### Constant Factor

Reshuffle Questions
Get Links to Questions